High-resolution paleoclimate reconstruction of the last 9000 years based on speleothem isotope records from northeastern Venezuela - Martinez Medina, Nathalie Melissa (2022)
Few high-resolution paleoclimate proxy records exist in the region located under the direct influence of the Inter-tropical Convergence Zone (ITCZ) in South America (SA); most of them retrieved from the Cariaco Basin (CB) off the coast of Venezuela. Here we present new high-resolution 18O and 13C records of speleothems collected in caves in the region adjacent to the CB in Venezuela, covering the Mid and Late Holocene. We document previously undetected multidecadal- to secular-scale climate variability in the core region of the ITCZ, which is being compared to other high-resolution records from the North Atlantic (NA), Caribbean and southern tropical South America. We show that the northeastern Venezuelan Holocene hydroclimate variability and the input of nutrients, productivity and oxygen demand in the CB has primary (but not exclusively) responded to NA climate (Bond cycles). However, the magnitude of those events and the background insolation conditions might have been the main determinants. Increased Northern Hemisphere (NH) insolation during the Mid-Holocene likely led to mostly in-phase relation between Venezuela and eastern Caribbean records (i.e. wet conditions occurred between 8.1-6.5 ka despite coinciding with Bond 5, due to the enhanced NH insolation and northward position of the ITCZ, whereas dry conditions were observed during the strongest of the Bond Cycles (4) around 5.5 ka). In addition, the comparison between the speleothem record of this study and other ones suggest that ITCZ stayed between Venezuela and Barbados as a narrower band during weaker and shorter events such as the Bond 3 with drying conditions observed to the north in Cuba and to the south in Peru. Our NE Venezuela record from Caripe Cave considerable differs from the Cariaco Basin Ti record during the last 2.3 ka. Pointing to non-previously reported relations to Caribbean and southern hemisphere tropical high-resolution records. During this period an out-phase relation is observed between Venezuela and Caribbean records and rather appears to be closely related to the South American Monsoon System (SAMS) dynamics. Contrary to results from previous studies in Cariaco, our results point out to drier conditions during Medieval Climate Anomaly (MCA, 900-1100 CE) close to the coast in Venezuela. No speleothem deposition occurred during most of Little Ice Age (LIA) which might be related to dryer conditions in response to a southward position that led to major moisture income to the SASM domain.